Analysis of the Impact of Load Change on the Efficiency of the Heat Exchanger on Closed-circuit Cooling Water with a Capacity of 300 MW - Nabila, Lathifa Dylla; Apriandi, Nanang; Herlambang, Yusuf Dewantoro; Surindra, Mochamad Denny (Eksergi, 2024)
Electricity has become one of the most crucial components of life. The steam power plant (PLTU) is the most significant contributor to the power supply process in Indonesia, with an installed capacity of 29.57%. A review of each component is required to support the sustainability of the production process at PLTU. This research discusses the heat exchanger's components in the refrigeration system at PT. XYZ. The cooling system in PLTU plays a vital role in preventing overheating of the power plant components, which can cause an interruption of the energy generation process. Following this, research was carried out on the influence of load changes on the efficiency of heat exchangers in PT. XYZ cooling systems using observation methods, interviews, and literature studies. Such methods produced data that could be used to calculate the efficiency value. From the results of the investigation, it was concluded that the performance of the PT. XYZ heat exchanger was at its best at maximum load with an efficiency presentation of 68.29% and at its lowest at minimum load with an effectiveness presentation of 59.95%. However, the value was still below the standard value of efficiency of the heat exchangers, which is 75%, so it required more intensive treatment to improve its efficiency value.